P84 Apnoeic event in wolf-hirschhorn syndrome: could this have been a 'Tet' spell?. (June 2019) - Maduemem, Kene; Arumugam, Gheetha; Chingale, Amol
Abstract : Background: Wolf-Hirschhorn syndrome (WHS) is a rare genetic condition caused by partial deletion of short arm of chromosome 4. Clinical manifestations comprise but not limited to typical facie, mental retardation, growth delay, epilepsy, and congenital cardiac defects. Congenital heart defects occur in about 25–50% of cases. We describe a child with WHS presenting with a femoral fracture; he became apnoeic in the course of management resulting in a cascade of events. Case Report: 4.5-year-old boy known to have WHS was admitted with left femoral fracture. The syndrome was an antenatal diagnosis. Other associations noted were severe growth delay (weight of 6 kg), epilepsy, global developmental delay, visual impairment, and tetralogy of Fallot (TOF). His TOF has been managed uneventfully on propranolol with acceptable oxygen saturation (Sp02) in the 70s. The spontaneous fracture required Gallows traction, which provoked distress. He developed hypoxic crisis requiring oxygen therapy to maintain acceptable SpO2. Subsequently, he went apnoeic and dusky needing bag and mask ventilation. Blood gas revealed severe metabolic acidosis, which improved after fluid bolus. Morphine dosing regimen for pain control was continued. Knee-chest position could not be attempted due to the fracture. Although he got treated for suspected sepsis due to the dilemma of events, he did have a hypercyanotic spell in hindsight. He was subsequently discharged with conservative management of the fracture. Conclusion: To the best of our knowledge, this is the first reported case of hypercyanotic (Tet) spell in WHS. This rather uncommon event resulted in a significant learning point for medical and nursing staff.